Antiplatelet therapy after coronary intervention in Asia and Japan - Goto, S.; Toda, E. (Hämostaseologie, 2009)
Currently available clinical database was mostly developed in North America and Europe (Western Countries). Clinical database of Asian patients are still not large enough to develop Asian region specific clinical guidelines, although the population of patients in the majority of Asia countries are increasing rapidly. Marked ethnic and life-style heterogeneity within Asian region also makes it difficult to develop Asian region specific Evidence-based clinical practice guidelines. In general, there are certain differences in the background epidemiology of the athero-sclerotic and thrombotic diseases in Asia countries and Western ones such as Asian patients are more prone to cerebrovascular disease (CVD) than coronary artery disease (CAD). Accordingly, there also are marked differences in the use of antiplatelet agents in Asian patients underwent coronary intervention (such as frequent use of cilostazol) as compared to those living in the Western countries. Currently available database also suggests the difference in side effects of anti -platelet agents in Asian patients as compared to Western ones such as relatively high incidence of hepatic dysfunction with the use of thienopiridine. In the future, it would be important to clarify the detailed difference of Asian patients and Western ones in regards to the effects and side effects of antiplatelet therapy by the multi-national prospective observation registry and clinical trials including equal number of Asian and Western patients. It would also be important for Asian physician to develop scientifically valid methods to import the results of “Global Evidence” with appropriate modification for the clinical practice in patients living in the specific region of Asia.
Keywords: Antiplatelet agents; Asia; Japan; aspirin; ticlopidine; clopidogrel; atrial fibrillation; intracranial bleeding